6-Gingerol-Rich fraction from Zingiber officinale prevents hematotoxicity and oxidative damage in kidney and liver of rats exposed to Carbendazim (2016)
Ginger (Zingiber officinale) is a globally marketed flavoring agent and cooking spice with a long history of human health benefits. The fungicide carbendazim (CBZ) is often detected in fruits and vegetables for human nutrition and has been reported to elicit toxic effects in different experimental animal models. The present study investigated the protective effects of 6-Gingerol-rich fraction (6-GRF) from ginger on hematotoxicity and hepatorenal damage in rats exposed to CBZ. CBZ was administered at a dose of 50 mg/kg alone or simultaneously administered with 6-GRF at 50, 100, and 200 mg/kg, whereas control rats received corn oil alone at 2 mL/kg for 14 days. Hematological examination showed that CBZ-mediated toxicity to the total white blood cell (WBC), neutrophils, lymphocytes, and platelets counts were normalized to the control values in rats co-treated with 6-GRF. Moreover, administration of CBZ significantly decreased the activities of superoxide dismutase, catalase, glutathione peroxidase, and glutathione S-transferase as well as glutathione level in the livers and kidneys of rats compared with control. However, the levels of hydrogen peroxide (H2O2) and malondialdehyde were markedly elevated in kidneys and livers of CBZ-treated rats compared with control. The significant elevation in the plasma indices of renal and hepatic dysfunction in CBZ-treated rats was confirmed by light microscopy. Coadministration of 6-GRF exhibited chemoprotection against CBZ-mediated hematotoxicity, augmented antioxidant status, and prevented oxidative damage in the kidney and liver of rats.